Microcycles of Violence: Evidence from Terrorist Attacks by ETA and the FMLN - Behlendorf, Brandon (Journal of quantitative criminology, 2012)
Recent research has demonstrated that individual crimes elevate the risk for subsequent crimes nearby, a phenomenon termed “near-repeats.” Yet these assessments only reveal global patterns of event interdependence, ignoring the possibility that individual events may be part of localized bursts of activity, or microcycles . In this study, we propose a method for identifying and analyzing criminal microcycles; groups of events that are proximate to each other in both space and time. We use the Global Terrorism Database (GTD) to analyze over 4,000 terrorist attacks attributed to the FMLN in El Salvador and the ETA in Spain; two terrorist organizations that were both extremely active and violent but differed greatly in terms of history, grievances and motives. Based on the definition developed, we find strong support for the conclusion that many of the terrorist attacks attributed to these two distinctive groups were part of violent microcycles and that the spatio-temporal attack patterns of these two groups exhibit substantial similarities. Our logistic regression analysis shows that for both ETA and the FMLN, compared to other tactics used by terrorists, bombings and non-lethal attacks are more likely to be part of microcycles and that compared to attacks which occur elsewhere, attacks aimed at national or provincial capitals or areas of specific strategic interest to the terrorist organization are more likely to be part of microcycles. Finally, for the FMLN only, compared to other attacks, those on military and government targets were more likely part of microcycles. We argue that these methods could be useful more generally for understanding the situational and temporal distribution of crime.